ANALISIS STRATEGI PEMBERANTASAN KORUPSI DI INDONESIA DALAM PERSFEKTIF HUKUM ADMINISTRASI NEGARA - Nabilah Ratna Dewi (JOURNAL IURIS SCIENTIA, 2023)
In Indonesia, corruption has become an open secret and has broad implications in people's lives. Corruption is one form of abuse of authority so that it intersects with administrative law which has an important role to supervise the government. This paper aims to analyze strategies to eradicate corrupt practices in Indonesia based on state administrative law. The research method used in this paper is juridical normative. Based on the results of the discussion, it can be concluded that the functions and roles of the State Administration Law in eradicating corruption in Indonesia, including: (1) Legal supervision of government administration and (2) Bureaucratic reform. Strengthening the State Administration Law is important as one of the effective options as a form of prevention and eradication of corrupt practices in Indonesia. There are several strategies to eradicate corrupt practices in Indonesia based on the State Administration Law, including: (1) Forming a leadership spirit for good governance, (2) Improving government administration institutions, (3) Strengthening the law, (4) Improving the integrity and ethics of state administration, and (5) Establishment and strengthening of Anti-Corruption Institutions.